Pharmacological Boosting Effect and Inhibitory Mechanism of Cobicistat and Ritonavir on Human Cytochrome P450 Isoforms. - Tran, Timothy. (2017)
Abstract: Abstract Pharmacokinetic boosting is the result of one drug increasing another co-administered drug's serum concentration to achieve a therapeutic effect. Here in this study, two protease inhibitor (PI) class drugs used in treatment of HIV that have boosting effects are evaluated for their potency and mechanism of inhibition on cytochrome P450 isoforms. Ritonavir is a widely used pharmaco-enhancer; often boosting serum concentration of another co-administered PI for HIV treatment. Cobicistat, recently approved for drug market has similar properties to ritonavir in boosting other PIs for HIV treatment. However, the mechanism of inhibition on CYP enzymes is unknown for cobicistat. Cobicistat can take a time-dependent inhibition (TDI) or reversible inhibition, however the inhibition route has not yet been established. In this study two IC50 assay with different incubation procedures are used in order to determine the mechanism of inhibition. A pre-incubation vs. no-pre incubation IC50 assay is performed with probe substrate to determine whether there is a shift in IC50. Cobicistat did not display a time dependent inhibition, similar to ritonavir, with CYP 1A2 and CYP 2C9. Furthermore, ritonavir and cobicistat are not potent inhibitors if CYP 1A2 after determining the IC50 values.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisors: David Greenblatt, and Margery Beinfeld.; Keyword: Pharmacology.